Central African Economic and Monetary Community : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, and Banking Supervision. (IMF Staff Country Reports; Country Report, 2006)
This Financial System Stability Assessment on the Central African Economic and Monetary Community (CEMAC) discusses the overall assessment of stability, integration, and development issues of the financial sector. The paper reviews plans to strengthen the prudential and systemic liquidity frameworks and the macroeconomic risks affecting the financial sector. It also provides summary assessments of the Reports on the Observance of Standards and Codes on monetary and financial policy transparency and banking supervision.